Library automation and the training needs of 21st century professionals: trend and challenges in academic library (2020)
Library automation is a key feature of the 21st-century library as it provides better management of library operations and Services through computerization and networking. It has become the tinkle word in the library profession and a target necessity for training and development of library Professionals. A well-trained librarian would make better and economic use of hardware and Software facilities which would go a long way to aid the full-scale automation of the library. Hence, this article focused on library automation trend and the training needs of 21bl- century library Professionals for full automation of academic libraries in Nigeria. It revealed the key challenges to effective automation of academic libraries and the need to enhance the proficiency of library Professionals in Nigeria. Conclusion and recommendations were highlighted among which were; mobilizing Tertiary Education Trust Fund allocation for an academic library to fund automation project and subsequent provision of adequate budgetary allocation for training and development of libraries in the 21st Century, setting up a committee to plan, implement and maintain the development of library automation, orienting library Professionals on the need for library automation training and retraining of all the staff that are involved in the automation Service Provision chain.